FTIR - An Essential Characterization Technique for Polymeric Materials - Barrios, Vladimir A. Escobar; Méndez, José R. Rangel; Aguilar, Nancy V. Pérez; Espinosa, Guillermo Andrade; Rodríguez, José L. Dávila (IntechOpen, 2012)
None